2015
DOI: 10.2106/jbjs.n.01311
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin Exposure Impairs BMP-2-Mediated Spinal Fusion in a Rat Arthrodesis Model

Abstract: Development of a pharmacologic agent that reduces the adverse effects of cigarette smoke on bone-healing could prove useful to orthopaedic surgeons. Since dioxin and other similar cigarette smoke toxins exert their effects through Ahr pathway activation, the receptor represents a potential therapeutic target to improve spinal fusion rates in patients who smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Dioxin, a minor hydrocarbon constituent of cigarette smoke but potent activator of the AhR, is thought to exert its effects almost exclusively through the receptor [ 20 , 21 ]. Because of its extremely high affinity for the receptor, dioxin is frequently used as a prototypical ligand to investigate the effects of the AhR pathway involvement in biological processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dioxin, a minor hydrocarbon constituent of cigarette smoke but potent activator of the AhR, is thought to exert its effects almost exclusively through the receptor [ 20 , 21 ]. Because of its extremely high affinity for the receptor, dioxin is frequently used as a prototypical ligand to investigate the effects of the AhR pathway involvement in biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that chronic exposure to dioxin inhibited bone morphogenetic protein 2 (BMP-2) mediated bone regeneration and posterolateral (L4–L5) spine fusion in the rat [ 21 ]. This study was the first to suggest a link between AhR activation and the reduced healing rates seen in smokers after spinal arthrodesis.…”
Section: Introductionmentioning
confidence: 99%
“…The Ahr plays an important role in xenobiotic metabolism, and previous studies have shown that pathway hyper-activation can have deleterious effects on bone biology (Singh et al, 2000, Jamsa et al, 2001, Naruse et al, 2002, Ryan et al, 2007). A proportionately minor constituent of CS, dioxin is a prototypical ligand frequently used to study Ahr involvement in biological activities, due to its extremely high affinity for the receptor and the widely-accepted belief that dioxin acts primarily through this mechanism (Hsu et al, 2015). Dioxin has previously been shown to inhibit some markers of osteoblastic differentiation in established murine cell lines (Singh et al, 2000, Ryan et al, 2007, Carpi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent work showed that dioxin exposure inhibits spine fusion in the rat (Hsu et al, 2015). With the present study, we sought to elucidate the underlying mechanisms of dioxin-mediated effects on bone regeneration using rat primary BMSC, and to explore the capacity of Ahr antagonists as potential agents to mitigate these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation